Profiling for Bioactive Peptides and Volatiles of Plant Growth Promoting Strains of the Bacillus subtilis Complex of Industrial Relevance - Mülner, Pascal; Schwarz, Elisa; Dietel, Kristin; Junge, Helmut; Herfort, Stefanie; Weydmann, Max; Lasch, Peter; Cernava, Tomislav; Berg, Gabriele; Vater, Joachim (Frontiers in Microbiology, 2020)
Plant growth promoting rhizobacteria attain increasing importance in agriculture as biofertilizers and biocontrol agents. These properties significantly depend on the formation of bioactive compounds produced by such organisms. In our work we investigated the biosynthetic potential of 13 industrially important strains of the Bacillus subtilis complex by mass spectrometric methodology. Typing of these organisms was performed with MALDI-TOF mass spectrometry followed by comprehensive profiling of their bioactive peptide products. Volatiles were determined by gas chromatography-mass spectrometry.Representative products of the members of the B. subtilis complex investigated in detail were: the surfactin family (surfactins, lichenysins, pumilacidins); the iturin family (iturins, mycosubtilins and bacillomycins); plantazolicin and the dual lantibiotic lichenicidins, as well as a wide spectrum of volatiles, such as hydrocarbons (alkanes/alkenes), alcohols, ketones, sulphur-containing compounds and pyrazines. The subcomplexes of the B. subtilis organizational unit; a) B. subtilis/B. atrophaeus; b) B. amyloliquefaciens/B. velezensis; c) B. licheniformis and d) B. pumilus are equipped with specific sets of these compounds which are the basis for the evaluation of their biotechnological and agricultural usage. The 13 test strains were evaluated in field trials for growth promotion of potato and maize plants. All of the implemented strains showed efficient growth stimulation of these plants. The highest effects were obtained with B. velezensis, B. subtilis and B. atrophaeus strains.